Prediction of progression to muscle-invasive disease in patients with high-risk bladder cancer - Oszczudlowski, Maciej; Dobruch, Jakub (Translational Andrology and Urology, 2018)
Despite complete transurethral resection of bladder tumor (TURBT) and adjuvant intravesical treatment, relevant proportion of patients with non-muscle invasive bladder cancer (NMIBC) experience disease recurrence or progression (1).